2010
DOI: 10.1074/jbc.m110.124255
|View full text |Cite
|
Sign up to set email alerts
|

RNA-binding Protein Muscleblind-like 3 (MBNL3) Disrupts Myocyte Enhancer Factor 2 (Mef2) β-Exon Splicing

Abstract: Mammalian MBNL (muscleblind-like) proteins are regulators of alternative splicing and have been implicated in myotonic dystrophy, the most common form of adult onset muscular dystrophy. MBNL3 functions as an inhibitor of muscle differentiation and is expressed in proliferating muscle precursor cells but not in differentiated skeletal muscle. Here we demonstrate that MBNL3 regulates the splicing pattern of the muscle transcription factor myocyte enhancer factor 2 (Mef2) by promoting exclusion of the alternative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 45 publications
1
39
1
Order By: Relevance
“…5F). These results suggested that MBNL3 represses adult pattern RNA isoforms, as has been proposed previously (Lee et al 2010). In agreement, Mbnl3 knockout myoblasts also displayed early changes in mRNA abundance compared with wild-type controls (Supplemental Fig.…”
Section: Congenital Myopathy and Spliceopathy In Mbnl1; Mbnl2 Double-supporting
confidence: 76%
“…5F). These results suggested that MBNL3 represses adult pattern RNA isoforms, as has been proposed previously (Lee et al 2010). In agreement, Mbnl3 knockout myoblasts also displayed early changes in mRNA abundance compared with wild-type controls (Supplemental Fig.…”
Section: Congenital Myopathy and Spliceopathy In Mbnl1; Mbnl2 Double-supporting
confidence: 76%
“…Using a DM1 cell culture model and DM1 patient tissue, they provided evidence that expression of CUG expanded RNAs can lead to an increase in MBNL3 expression accompanied by a decrease in Mef2D β-exon splicing (Lee et al, 2010). These studies suggest that an increase in MBNL3 activity may play a role in the skeletal muscle degeneration experienced by DM1 patients (Lee et al, 2010).…”
Section: Myocyte Enhancer Factor 2 (Mef2)mentioning
confidence: 93%
“…MBNL3 antagonizes muscle differentiation by disrupting the expression of (+)β isoform of Mef2D which is transcriptionally more active (Lee et al, 2010). Using a DM1 cell culture model and DM1 patient tissue, they provided evidence that expression of CUG expanded RNAs can lead to an increase in MBNL3 expression accompanied by a decrease in Mef2D β-exon splicing (Lee et al, 2010).…”
Section: Myocyte Enhancer Factor 2 (Mef2)mentioning
confidence: 99%
See 1 more Smart Citation
“…The subnuclear localization pattern of MBNL3 in interchromatin regions supports our discovery that MBNL3 is a regulator of pre-mRNA splicing in myogenic cells. (17) Discussion Mammalian MBNL proteins have been implicated in muscle differentiation based on their homology to muscleblind, a Drosophila protein required for terminal muscle differentiation in flies. (18) The existence of three MBNL genes in vertebrates as opposed to a single gene in Drosophila implies that there are functional differences between the three mammalian MBNL proteins MBNL1, MBNL2, and MBNL3.…”
mentioning
confidence: 99%